2017
DOI: 10.1016/j.bonr.2017.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Long-term treatment with odanacatib maintains normal trabecular biomechanical properties in ovariectomized adult monkeys as demonstrated by micro-CT-based finite element analysis

Abstract: The cathepsin K inhibitor odanacatib (ODN) is a potent and reversible inhibitor of osteoclastic resorption activity. This drug is currently under development for the treatment of postmenopausal osteoporosis. Previously, we described data on the treatment efficacy of ODN in a preclinical estrogen-deficient model of an ovariectomized (OVX) rhesus monkey using HR-pQCT based finite element analysis (FEA) in vivo estimates of bone strength on the distal radius. To support the bone safety profile of ODN, we report e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Ex vivo volumetric measures of total and trabecular BMD and BMC of vertebral bodies (LV4 and LV5) were obtained from a 0.8 mm-thick slice taken from the middle of each vertebral body excised for biomechanical testing ( Duong et al, 2016a ). Another vertebral site (LV2) was further subjected to μCT scanning at an isotropic 20 μm resolution using a Scanco μCT-40 scanner (Scanco Medical AG, Brütisellen, Switzerland) as previously described ( Cabal et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…Ex vivo volumetric measures of total and trabecular BMD and BMC of vertebral bodies (LV4 and LV5) were obtained from a 0.8 mm-thick slice taken from the middle of each vertebral body excised for biomechanical testing ( Duong et al, 2016a ). Another vertebral site (LV2) was further subjected to μCT scanning at an isotropic 20 μm resolution using a Scanco μCT-40 scanner (Scanco Medical AG, Brütisellen, Switzerland) as previously described ( Cabal et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…The increase in bone density created significant scientific interest in targeting the enzymatic activity of the CTSK gene to increase bone density in patients with osteoporosis [23,[29][30][31][32][33]. Bone et al [32] and Pirapaharan et al [34] concluded in their studies that low doses of cathepsin K inhibitors increase the levels of CTSK; however, higher doses decrease these levels.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, more than 16,000 patients received odanacatib 50 mg weekly, which increased BMD at the lumbar spine and total hip after 5 years by 11.2 and 9.5% in the phase III trial, respectively, and reduced the risk of hip fracture by 47%, non-vertebral fractures by 23%, and clinical vertebral fractures by 72% 70 , 71 . However, odanacatib has been discontinued due to a small increased risk of stroke in the postmenopausal patients, even possessing robust efficacy for treatment of osteoporosis 72 , 73 .…”
Section: Cat K Inhibitorsmentioning
confidence: 99%